Molecular Mechanisms of Leukocyte Migration and Its Potential Targeting—Lessons Learned From MKL1/SRF-Related Primary Immunodeficiency Diseases - Sprenkeler, Evelien G. G.; Guenther, Carla; Faisal, Imrul; Kuijpers, Taco W.; Fagerholm, Susanna C. (Frontiers in Immunology, 2021)
Megakaryoblastic leukemia 1 (MKL1) deficiency is one of the most recently discovered primary immunodeficiencies (PIDs) caused by cytoskeletal abnormalities. These immunological “actinopathies” primarily affect hematopoietic cells, resulting in defects in both the innate immune system (phagocyte defects) and adaptive immune system (T-cell and B-cell defects). MKL1 is a transcriptional coactivator that operates together with serum response factor (SRF) to regulate gene transcription. The MKL/SRF pathway has been originally described to have important functions in actin regulation in cells. Recent results indicate that MKL1 also has very important roles in immune cells, and that MKL1 deficiency results in an immunodeficiency affecting the migration and function of primarily myeloid cells such as neutrophils. Interestingly, several actinopathies are caused by mutations in genes which are recognized MKL(1/2)-dependent SRF-target genes, namely ACTB, WIPF1, WDR1, and MSN. Here we summarize these and related (ARPC1B) actinopathies and their effects on immune cell function, especially focusing on their effects on leukocyte adhesion and migration. Furthermore, we summarize recent therapeutic efforts targeting the MKL/SRF pathway in disease.